ANALISIS MUTU KUALITAS PELAYANAN PADA KONSUMEN RUMAH MAKAN KAPAU PAK NIN BATAM - Wahyudi Ilham; Tito Pratama; Dailami (Puslitabmas Batam Tourism Polytecnic, 2022)
In this study, the authors used a qualitative approach with a descriptive method. The sampling technique used in this research is purposive sampling. In purposive sampling technique. primary data sourced from field data collected directly by researchers at the restaurant